Al-Sheikh Abu Bakar al-Ashaari al-Malizi wamanhijah fi kitab 'intisari tafsir juzu'Amma - Adnan Mohd Yusuf, (Penerbit Universiti Kebangsaan Malaysia, 2011)
﻿Al-Sheikh Abu Bakar al-Ashaari is considered as one of the modern lslamic scholars who are very active in calling for reformations in religious life of Muslim society in Malay Archipelago, in order to create the civilised society as needed. He devotes all his efforts and strengths to achieve this hope through the speech, books, and prubic services. The book, 'Intisari Tafsir Juzu 'Amma :written by him is the complete exegesis of the last chapter of al-Qur 'an and it is one of his contributions to society through writing to correct people understanding and raise their conciousness and spirit to achieve the ambition. He uses an interesting approach and special methodology in his book to reform the religious life of Muslim society in this region. The purpose of this research is to study the methodology implemented by al-Sheikh Abu Bakar Ashaari in his book and present it to readers with the examples. It is also to analyse the relation between his methodology and other scholars methodology in the context of exegesis discipline in the global level. It is a library research which is based on the deep study on the book and related analytical aspects through historical exegesis books. This study resulted that al-Sheikh Abu Bakar Ashaari has combined Salaf methodology and current need of sociefy The study also found that his methods have strong relation with the development of exegesis discipline and its scholars. HopefuIly this research could highlight one of Malaysian exegesis scholars and show the real view about the Qur'anic exegesis movement and its standing in the context of development generally in this region which is located far from knowledge evolution centre and lslamic scholars especially Qur 'anic interpretators.